2010
DOI: 10.1037/a0019969
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Coping with Discrimination Scale: Factor structure, reliability, and validity.

Abstract: Four studies were conducted to develop and validate the Coping With Discrimination Scale (CDS). In Study 1, an exploratory factor analysis (N = 328) identified 5 factors: Education/Advocacy, Internalization, Drug and Alcohol Use, Resistance, and Detachment, with internal consistency reliability estimates ranging from .72 to .90. In Study 2, a confirmatory factor analysis (N = 328) provided cross-validation of the 5-factor model as well as evidence for validity of the scale. The validity evidence was similar ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
178
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(192 citation statements)
references
References 64 publications
14
178
0
Order By: Relevance
“…Initially, using angered confrontation predicted lower well-being than when using indirect confrontation. This is consistent with non-diary work examining confrontation at one point in time, showing confrontation is associated with decreased victim well-being (Bergman et al, 2002;Foster, 2009a;Wei et al, 2010). This may not be surprising given the social costs of confronting a perpetrator (e.g., Kaiser & Miller, 2001); if confrontation elicits negativity from the perpetrator and observers, then the victim may suffer interpersonal repercussions again.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Initially, using angered confrontation predicted lower well-being than when using indirect confrontation. This is consistent with non-diary work examining confrontation at one point in time, showing confrontation is associated with decreased victim well-being (Bergman et al, 2002;Foster, 2009a;Wei et al, 2010). This may not be surprising given the social costs of confronting a perpetrator (e.g., Kaiser & Miller, 2001); if confrontation elicits negativity from the perpetrator and observers, then the victim may suffer interpersonal repercussions again.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, Pennebaker and others have shown that by expressing emotions, well-being improves over time (e.g., Campbell & Pennebaker, 2003;Frisina, Borod & Lepore, 2004;King & Miner, 2000). As such, although confrontations that involve direct communication to the perpetrator may be difficult initially and may lower well-being at one point in time (e.g., Bergman et al, 2002;Foster, 2009a;Wei et al, 2010) the benefits of direct confrontations may be seen after some time to the extent that such confrontations involve being able to express oneself. As such, Hypothesis 1 states: continued use of direct confrontations will be associated with increasing well-being over time.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural equation models were used to fit the separate regressions for each of the consumer behaviors using as a predictor (a) MEIM-Total, (b) AEI alone, and (c) AEI and BEI together. Maximum likelihood (ML) estimation was carried out using Mplus version 6.1 (Muthén & Muthén, 1998-2010. Each application of the MEIM was evaluated as a predictor of the consumer behaviors, with effect size measured by adjusted R 2 , the proportion of variance accounted for in the outcome: Adjusted R 2 = (1 2 residual variance)/sample variance of Y. Two-tailed tests with Bonferroni adjustments were applied to the nine consumer behavior items (each test evaluated at a = .05/9 = .0056) and the two language preference items (each test evaluated at .05/2 = .025).…”
mentioning
confidence: 99%